Male livestock fertility: boar & bull management considerations - Hartman, Ashley Renae (Kansas State University, 2023)
Male livestock fertility is a vital component of efficient reproduction and significantly impacts the profitability of production systems. Over the last several decades, substantial strides have been made regarding the understanding of female fertility, but relative to females, research in male reproductive management is sparse. In swine and cattle production systems, the male can impact thousands of offspring and significantly impact future generations, drawing attention to the value of understanding if and how development and management of male breeding stock affects fertility. The studies within this dissertation contribute to the body of knowledge on bull and boar management practices and subsequent reproductive outcomes. In the first study, we aimed to assess the effects of percentage body weight change in developing Duroc boars on semen collection training, semen production parameters, and longevity in a commercial boar stud. Retrospectively, 164 boars were divided into one of three groups based on their percentage body weight change from arrival to the boar stud until the end of the 42-day isolation period. The one-third of boars that had the greatest percentage of body weight change during the isolation period gained 36.1% to 10.1% (TOP). The middle one-third of boars that were intermediate in percentage body weight change during isolation gained 9.7% to 2.6% (MIDDLE). The final group consisted of one-third of boars that either minimally gained or lost weight (2.5% to -9.5% change in body weight; BOTTOM). Boars were observed for six months to evaluate the impact of percent body weight change during the 42-day isolation period on semen parameters and longevity. Boars in the TOP group lost the least amount of backfat (indicated by ultrasound or caliper score) (P < 0.05), while boars in the BOTTOM group lost the most backfat of the three groups. Average boar age at the time of successfully becoming a working boar (successfully mounting the collection dummy and producing an ejaculate with a motility ≥ 70% and percent normal morphology ≥ 65%) and the proportion of boars that were successful at become working boars did not differ between groups (P > 0.05). Among working boars, the concentration of sperm in ejaculates tended to differ (P = 0.0740) between groups. Boars in the TOP group had a greater percentage of sperm with normal morphology (P = 0.0337) than boars in the BOTTOM group. There was a group by production week interaction (P < 0.0001) for semen ejaculate volume, total number of sperm, and total number of sperm with normal morphology. Boars in the TOP and MIDDLE groups produced more total sperm and normal sperm than the BOTTOM group from weeks 8 to 20 of being working boars. During their time as working boars, of boars that were either culled from the stud or died, and there was no difference (P > 0.05) among groups. While there were no differences in semen collection training and longevity in the stud, the increase in production of total normal sperm in the TOP and MIDDLE groups compared with the BOTTOM group could have substantial economic benefits for boar studs. In the second study our objective was to determine the relative percentages of calves sired by either natural service sires or fixed time artificial insemination (FTAI) sires within the same estrous period. During 2 consecutive years heifers and cows (heifers: n = 141; cows: n = 191) had estrous cycles synchronized and were inseminated following the 7-day CO-Synch + CIDR FTAI protocol. Females were inseminated by one AI technician using a single sire for heifers and a different single sire for cows. All females were exposed to natural service bulls immediately following AI. After calving, DNA was collected from a random subset of calves (Calves born from heifers in Year 1: n = 59 and Year 2: n = 82; Calves born from cows in Year 1: n = 89 and Year 2: n = 102) born in the first 21 day of the calving season to determine sire parentage. In Year 1 among calves born from heifers, the percentage sired by natural service was 5.1% (n = 3/59). Among calves born from cows, the percentage sired by natural service was 14.6% (n = 13/89). In Year 2 among calves born from heifers, the percentage sired by natural service was 9.8% (n = 8/82). Among calves born from cows, the percentage sired by natural service was 20.6% (n = 21/102). If commercial producers use FTAI followed by immediate bull exposure in cows, natural service bulls may sire more calves early in the calving season than expected. When using these practices in heifers, natural service bulls sired a lesser proportion of the calves than observed in cows. The objective of the third study was to compare breeds and evaluate correlations of sperm quality assessments observed during yearling beef bull breeding soundness exams (BSE). Ejaculates were collected via electroejaculation from yearling Charolais (n=23) and Angus (n=23) bulls as part of BSEs. One veterinarian conducted BSEs, and one technician conducted sperm quality assessments. Additional sperm motility analysis was conducted with the iSperm. Ejaculates meeting minimum thresholds for passing a BSE were subjected to flow cytometry to measure sperm functional traits. Pearson’s correlation coefficients were determined, and breed comparisons were made using GLIMMIX in SAS. The iSperm analyzer gross and progressive motilities were (r = 0.30; 0.38; P < 0.001) correlated with technician progressive motility. Neither iSperm (P = 0.26) nor visual assessment (P = 0.66) of sperm motility differed among breeds. Bull breed did not influence (P = 0.83) total percentage of viable cells, percentage of viable cells with intact acrosomes (P = 0.83), or percentage of live sperm cells (P = 0.92) with positive reactive oxygen species (ROS) status. There was a tendency (P = 0.10) for greater percentage of sperm from Charolais bulls (31.1% ± 3.35) to have positive mitochondrial energy potential as compared with Angus bulls (17.6% ± 3.35). The percentage of live spermatozoa with negative ROS status was moderately correlated with the percentage of spermatozoa exhibiting secondary abnormalities (r = 0.33; P = 0.02). Percentage of live spermatozoa with disrupted acrosomes was strongly correlated (r = 0.66; P < 0.001) with percentage of live spermatozoa with negative ROS. Percentage of live spermatozoa with positive ROS status was correlated (r = 0.58; P < 0.001) with percentage of spermatozoa with active mitochondrial membranes. Technician and iSperm sperm motility are positively correlated, offering producers an on-farm evaluation tool. Though bull breed had little influence on sperm quality assessments in this experiment, ROS in sperm appeared to impair sperm health and function. The fourth study investigated the potential impacts of concurrent enrollment of undergraduate students in lecture and laboratory animal reproduction courses on final course percentages. Student learning outcomes and structure of the laboratory course were designed to provide hands-on learning opportunities, which coincided with concepts discussed in lecture. A total of 307 students were included in the analysis. Students concurrently enrolled in laboratory and lecture had a greater (P < 0.001) final course percentage in the lecture compared with those enrolled in lecture alone. Students in the science degree option had a greater (P < 0.03) final lecture course percentage compared with those in the production degree option, and juniors had a greater (P = 0.05) final course percentage when compared with sophomores. At the end of the semester, students were surveyed about the perceived value of the laboratory course on their learning. Among students enrolled in laboratory sections, 98.4% indicated the hands-on activities improved their knowledge of course concepts in lecture. These student beliefs are supported by our results, which suggest that taking the laboratory and lecture together improves student final course percentages and that students value the hands-on learning opportunities provided in laboratory sections.
Keywords: Beef bulls; Boars; Semen production; Animal reproduction; Cattle; Swine